Structural diversity and tree density drives variation in the biodiversity–ecosystem function relationship of woodlands and savannas. Issue 2 (11th August 2021) - Godlee, John L.; Ryan, Casey M.; Bauman, David; Bowers, Samuel J.; Carreiras, Joao M. B.; Chisingui, Antonio Valter; Cromsigt, Joris P. G. M.; Druce, Dave J.; Finckh, Manfred; Gonçalves, Francisco Maiato; Holdo, Ricardo M.; Makungwa, Steve; et al.
Summary: Positive biodiversity–ecosystem function relationships (BEFRs) have been widely documented, but it is unclear if BEFRs should be expected in disturbance‐driven systems. Disturbance may limit competition and niche differentiation, which are frequently posited to underlie BEFRs. We provide the first exploration of the relationship between tree species diversity and biomass, one measure of ecosystem function, across southern African woodlands and savannas, an ecological system rife with disturbance from fire, herbivores and humans. We used > 1000 vegetation plots distributed across 10 southern African countries and structural equation modelling to determine the relationship between tree species diversity and above‐ground woody biomass, accounting for interacting effects of resource availability, disturbance by fire, tree stem density and vegetation type. We found positive effects of tree species diversity on above‐ground biomass, operating via increased structural diversity. The observed BEFR was highly dependent on organismal density, with a minimum threshold of c . 180 mature stems ha −1 . We found that water availability mainly affects biomass indirectly, via increasing species diversity. The study underlines the close association between tree diversity, ecosystem structure, environment and function in highly disturbed savannas and woodlands. We suggest that tree diversity is an under‐appreciated determinant of wooded ecosystem structure and function.